TRANSFORMASI GERAKAN SOSIAL KE PARTAI POLITIK KIPRAH POLITIK PARTAI RAKYAT DEMOKRATIK DI MASA REFORMASI - Argenti, Gili (Departemen Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2016)
In the New Order era (Orde Baru), the end of the 1970s until the early 1990s, the student movement is faced with repressive measures, a policy of limiting the political activities of students applied, then the search for a new format motion is a must. The study group is an option to avoid the political power. In the expansion, the study group turns into a political party, the Peopleâs Democratic Party (PRD). The emergence of the PRD as an opposition party to the New Order Indonesian political public attention, because of their political program is so radical. Also, the communist stigma attached by the government to the partyâs young people reap the reaction of pro and cons in the community. After the collapse of the New Order, PRD became an electoral party but failed to reap the support of voters. This paper describes the process of changing the format of the student movement of the 1990s, from the study group into action committees, later became a political party, in this paper also described the political progress of PRD in the reform era.Â